Occupancy of different types of forest habitats by tyrant flycatchers (Passeriformes: Tyrannidae) - Rosa, Gabriel Lima Medina; Anjos, Luiz dos; Moura, Maurício Osvaldo (Biota Neotropica, 2013)
The abundance distribution of the tyrant flycatchers (Tyrannidae family) was evaluated in three main forest habitats of Mata dos Godoy State Park (PEMG), north of the state of Paraná. We conducted point counts and from the collected data we calculated the Index of Point Abundance (I. P. A.) of each species in the habitats of interior of mature forest (FLI), slope forest (FLE) and reforestation (REF). Among the 22 recorded species, eight occurred in all habitats, while other eight occurred in two habitats and six were exclusive of one habitat. Among the 16 recorded species in more than one habitat, 10 were more abundant in only one. On the contrary to our expectation and despite the clear habitat segregation among species, the abundance distribution was not significantly influenced by the foraging strategies. Maybe, phylogenetic relationships could better explain the found pattern. Some partially frugivorous species were present in REF and FLI. Those species could be considered as potential ecological restoration agents and thus to promote seed dispersal among habitats. Indeed, the greater similarity of tyrant flycatchers abundance distribution in FLI and REF indicates that these two habitats could be part of the same gradient. FLE, however, can be considered a separated habitat by its abundance of bamboo clusters and the six tyrant flycatcher species which are commonly associated with this vegetation type.